A prospective, single-blind, randomised, crossover study comparing three nasal hygiene systems and corresponding patient preference for such devices. Issue 1 (14th January 2014) - Elmiyeh, B; Heywood, R L; Prasad, V M N; Chatrath, P; Bassett, P; Quiney, R
Abstract: Objective: To assess subjective preference using three nasal hygiene systems: Stérimar Original ®, Emcur ® and Sinus Rinse™. Design: We used a prospective, single-blind, randomised, crossover study to compare three nasal hygiene systems: Stérimar Original, Emcur and Sinus Rinse. Subjects: Eighteen adult volunteers were recruited and were asked to rate their experience over three days using three well-established nasal hygiene systems. A standard visual analogue scale was used to assess five criteria: (1) simplicity of instructions; (2) ease of use; (3) comfort; (4) perceived nasal clearance (effectiveness) and (5) single best overall system. Results: Stérimar Original was found to have the easiest instructions to understand compared to the other two systems. There was no significant difference between Stérimar Original and Sinus Rinse with regards to ease of use but they were both significantly easier to use than Emcur ( p  < 0.05). There was no statistically significant difference between the three systems when comparing the last three criteria. There was no alteration in preference when the cost of each treatment was disclosed to the subjects, and no significant side effects were reported. Conclusion: The instructions accompanying Stérimar Original appeared to be the easiest to understand, while Stérimar Original and Sinus Rinse were easier to use than Emcur.